2010
DOI: 10.1891/0198-8794.30.233
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Illness, Family Comorbidity, and Cumulative Disadvantage<BR> <I>An Ethnographic Treatise on Low-Income Mothers' Health in Later Life</I>

Abstract: Using longitudinal ethnographic data on low-income families residing in Boston, Chicago, and San Antonio, we explore the ways in which childhood illness, family comorbidity, and cumulative disadvantage shape behavioral and social contexts for young mothers' physical and mental health in later life. Data are from the Three-City Study ethnography, which examined, over a 6-year period, the lives of 256 low-income Latino, African American, and White mothers and their children (N = 685). Grounded theory analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 56 publications
(78 reference statements)
0
12
0
Order By: Relevance
“…The challenges of balancing work, family responsibilities, and personal needs are especially acute for mothers with low education and unstable low-wage employment. A vicious cycle of problems can develop, such that these mothers neglect their ...the parenthood-happiness gap is signifi cantly greater in the United States than in 21 other OECD countries (Glass, Simon, & Andersson, in press own physical and mental health needs to meet their children's needs, increasing their risk of being fi red or forced to leave their jobs (Burton & Bromell, 2010). Chronic, unfavorable distal factors would be expected to have a direct effect on family stress, which might manifest itself in psychological distress in parents and in couples' distress.…”
Section: Workplace Practicesmentioning
confidence: 99%
“…The challenges of balancing work, family responsibilities, and personal needs are especially acute for mothers with low education and unstable low-wage employment. A vicious cycle of problems can develop, such that these mothers neglect their ...the parenthood-happiness gap is signifi cantly greater in the United States than in 21 other OECD countries (Glass, Simon, & Andersson, in press own physical and mental health needs to meet their children's needs, increasing their risk of being fi red or forced to leave their jobs (Burton & Bromell, 2010). Chronic, unfavorable distal factors would be expected to have a direct effect on family stress, which might manifest itself in psychological distress in parents and in couples' distress.…”
Section: Workplace Practicesmentioning
confidence: 99%
“…10 For example, in 1990, prior to HOPE VI implementation, Geronimus et al 11 found that black youth residing in high-poverty urban areas experienced 25 fewer years of active life expectancy compared with same-age white residents of socioeconomically moreadvantaged locales. Alarming as they are, such statistics understate the degree to which the urban poor experience "family comorbidity," 12 whereby multiple family members suffer concurrent physical and mental health problems. In their ThreeCities ethnographic study of low-income households, Burton and colleagues found that in 68% of the 255 participating families, both mothers and children reported multiple physical and mental health problems.…”
Section: Introductionmentioning
confidence: 99%
“…In their ThreeCities ethnographic study of low-income households, Burton and colleagues found that in 68% of the 255 participating families, both mothers and children reported multiple physical and mental health problems. 12 Specific to HOPE VI, studies of public housing residents have found a population of adults and children in extremely poor health. [13][14][15] For example, prior to relocation, female African American residents at HOPE VI sites experienced rates of diabetes, depression, asthma, and hypertension that were nearly twice as high as those found in national samples of African American women.…”
Section: Introductionmentioning
confidence: 99%
“…Periodic uncertainty qualifies as a minimal condition in this regard, but it is chronic uncertainty that more accurately describes the lives of poor and working-poor individuals and families (Harvey, 1993;Imig, Bokemeier, Keefe, Struthers, & Imig, 1997;Sapolsky, 2005;Wood, 2001Wood, , 2003. This unremitting kind of uncertainty-an inability to predict whether money will last until the end of the month, thorny relations with recalcitrant landlords, recurring sickness or unstable jobs that can disrupt whatever household stability has been achieved-often brings with it considerable anxiety and stress, comorbid physical and mental health problems (Burton & Bromell, 2010;Geronimus, Hicken, Keene, & Bound, 2006;Sapolsky, 2005), and the attendant dysphoria that prior research has indicated is another core feature of living under conditions of uncertainty (Antonovsky, 1979;Suls & Mullen, 1981). Many poor single mothers also have extensive life histories of domestic violence and sexual abuse (Macmillan, 2001).…”
Section: Social Worlds Of Poverty and Uncertaintymentioning
confidence: 99%